VARIATION IN RICE TUNGRO VIRUS TRANSMISSION ABILITY BY GREEN LEAFHOPPER, Nephotettix virescens DISTANT (HOMOPTERA: CICADELLIDAE) ON RICE RESISTANT VARIETIES - I Nyoman Widiarta; Adolf Bastian; Syahrir Pakki (Indonesian Journal of Agricultural Science, 2014)
Green leafhopper (GLH), Nephotettix virescens, is the most efficient vector of rice tungro virus disease. The disease is endemic in some provinces of Indonesia and commonly con-trolled using resistant varieties. Resistance of rice varieties to tungro could be classified into resistance to a virus and a vector. The history of GLH resistant varieties adoption affected the GLH adaptation in an area. The study was conducted in the period of 2009-2011 to evaluate the resistance status of five GLH resistant rice variety groups (T0-T4) using survival and transmission test. The GLH populations were collected from 15 tungro endemic provinces in Indonesia. The GLH was then reared in the greenhouse before used for the test. The degree of resistance to tungro viruses was calculated by adding the value of survival (weight x score of survival rate) and virus transmission rate (weight x score of transmission rate). The weights for survival and transmission rate were set to 40 and 60, respectively. The results showed that the rank of resistant variety groups in decreasing order of resistance were T4, T1, T2 and T3. Five variations in GLH transmission efficiency were identified, i.e. 170, 070, 050, 030 and 010. GLH populations from Bali and West Nusa Tenggara were the most efficient vector for rice tungro virus. We concluded that there were diversities in the degree of resistance among GLH resistant varieties. Variation in virus transmission efficiency (biotype) among GLH populations collected from various tungro endemic areas closely related to the history of adoption of rice varieties.